L’Imaginaire rural revisité dans la littérature de langue française : une approche écopoétique - Laure Coppieters (Catalonia)
The countryside has long been a source of inspiration for literature in France, a country where the idea of nature is linked to nature as worked by man. The rural world was a central theme in pastoral and regionalist novels, which offered an idealized vision of the «Petits pays». Freed from old clichés, the countryside is (re)finding its place in contemporary literature. However, this literature appears within the context of a different relationship to nature: ecology has become a major issue, and «the environment» has now replaced «the countryside». This reality forces us to take a closer look at ecopoetics, the study of literature as it relates to the environment.In this article, Laure Coppieters presents the ecopoetic approach in contrast to American ecocriticism. This comparison leads us to precise the specificity of a particularly French approach. As one of the merits of ecopoetics is that it has opened up the corpus, Laure Coppieters then analyses environmental texts focusing on the rural world. She looks at a series of works by authors ranging from J. Giono to G. Koenig, through P. Gascar, J-L. Trassard, C. Hunzinger and others. This representative overview is an opportunity to discover the development of environmental literature: the emergence of «green» literature, «brown» literature and militant literature. Particular attention is paid to the importance that ecopoetics attaches to the creative act of writing.